L' insurrection hongroise : questions aux militants du PCF - Lefort, Claude (Paris : S ou B, 1956)
Bibliotheek François Vercammen
Bijlage van Socialisme ou Barbarie, nr 20
Frans
Brochure
Keywords: Hongaarse Revolutie (1919)